Faster coroutine pipelines: A reconstruction. (3rd August 2020) - PIETERS, RUBEN P.; SCHRIJVERS, TOM
Abstract: The three-continuation approach to coroutine pipelines efficiently represents a large number of connected components. Previous work in this area introduces this alternative encoding but does not shed much light on the underlying principles for deriving this encoding from its specification. This paper gives this missing insight by deriving the three-continuation encoding based on eliminating the mutual recursion in the definition of the connect operation. Using the same derivation steps, we are able to derive a similar encoding for a more general setting, namely bidirectional pipes. Additionally, we evaluate the encoding in an advertisement analytics benchmark where it is as performant as pipes, conduit, and streamly, which are other common Haskell stream processing libraries.